Rural Vaccination Coverage Among Children Aged 12–23 Months Was Higher Than the Urban Counterparts: A Comparative Cross-Sectional Study in Pawi District, Ethiopia - Gelaye SS Snr; Yenit MK; Baraki AG (Dove Medical Press, 2021)
Smeneh Sintayehu Gelaye Snr,1 Melaku Kindie Yenit,2 Adhanom Gebreegziabher Baraki2 1Department of Maternal and Child Health, BenshangulGumuz Health Office, BenshangulGumuz, Ethiopia; 2Department of Epidemiology and Biostatistics, College of Medicine and Health Sciences, Institute of Public Health, University of Gondar, Gondar, EthiopiaCorrespondence: Adhanom Gebreegziabher Baraki Tel +251918068580Email adsh04@gmail.comBackground: In developing countries like Ethiopia, about 3 million children’s deaths are attributed to vaccine-preventable diseases. Studies especially that try to explain the urban to rural vaccination coverage discrepancy are limited in the study area. This study aimed to assess full vaccination coverage and associated factors among children aged 12– 23 months in rural and urban kebeles of Pawi district.Methods: A community-based comparative cross-sectional study among urban and rural kebeles was conducted. A multistage sampling method was used to select 456 rural and 229 urban. Data were collected from mothers/caregivers using interviewer-administered questionnaires and vaccination cards. Full vaccination coverage was estimated for both urban and rural kebeles. Multivariable logistic regression analysis was used to identify factors associated with full vaccination. Adjusted Odds Ratio with a 95% confidence interval was reported.Results: Full vaccination coverage was 67% (95% CI 63% − 71%) and 60% (95% CI: 54% − 66%) among rural and urban residents, respectively. Educational status of the father (AOR=2.69; 95% CI, 1.61– 4.48), using postnatal care (PNC) (AOR=2.60; 95% CI, 1.58– 4.29), discussion on side effect and contraindications of vaccines (AOR=1.82 95% CI, 1.16– 2.88), and Institutional delivery (AOR=4.39, 95% CI 2.17– 8.87) were factors significantly associated with full vaccination among rural children, whereas using Knowledge on immunization schedules (AOR=1.92 95% CI, 1.03– 3.60), PNC (AOR=3.19; 95% CI, 1.57– 6.47), discussion on side effects and contraindications of vaccines (AOR=2.75; 95% CI, 1.4– 5.3) were notably associated with full vaccination among urban children.Conclusion: The study reveals vaccination coverage was higher in rural compared to urban kebeles but it is still far below the WHO recommended target. Therefore interventions shall be made to improve the coverage especially by using the identified factors like improving PNC service and promoting institutional delivery and health education.Keywords: full vaccination, associated factors, comparative cross-sectional, Ethiopia